Answer

Verified

447.9k+ views

Hint- Use different trigonometric identities of combination of angles in order to solve the question, also keep in mind the RHS part for manipulation.

Complete step-by-step solution -

Given that: to prove $4\cos {12^0}\cos {48^0}\cos {72^0} = \cos {36^0}$

Since we know that

$2\cos A\cos B = \cos \left( {A + B} \right) + \cos \left( {A - B} \right)$

Taking the LHS part and proceeding further

$

LHS = 4\cos {12^0}\cos {48^0}\cos {72^0} \\

= 2 \times \left( {2\cos {{12}^0}\cos {{48}^0}} \right) \times \cos {72^0} \\

$

With the help of above formula simplifying the middle term

$

= 2 \times \left[ {\cos \left( {{{48}^0} + {{12}^0}} \right) + \cos \left( {{{48}^0} - {{12}^0}} \right)} \right] \times \cos {72^0} \\

= 2 \times \left[ {\cos \left( {{{60}^0}} \right) + \cos \left( {{{36}^0}} \right)} \right] \times \cos {72^0} \\

= 2\cos {60^0}\cos {72^0} + 2\cos {36^0} \times \cos {72^0} \\

$

Now substituting the value of know trigonometric quantity in the above equation

$

= 2 \times \dfrac{1}{2} \times \cos {72^0} + 2\cos {36^0}\cos {72^0}{\text{ }}\left[ {\because \cos {{60}^0} = \dfrac{1}{2}} \right] \\

= \cos {72^0} + 2\cos {36^0}\cos {72^0} \\

$

Again using the formula in second part

$

= \cos {72^0} + \left[ {\cos \left( {{{72}^0} + {{36}^0}} \right) + \cos \left( {{{72}^0} - {{36}^0}} \right)} \right] \\

= \cos {72^0} + \left[ {\cos {{108}^0} + \cos {{36}^0}} \right] \\

$

Also we know that

$

\cos \left( {180 - \theta } \right) = - \cos \theta \\

\Rightarrow \cos {108^0} = \cos \left( {{{180}^0} - {{72}^0}} \right) = - \cos {72^0} \\

$

So, substituting the value in above equation we have

$

= \cos {72^0} + \cos {108^0} + \cos {36^0} \\

= \cos {72^0} - \cos {72^0} + \cos {36^0}{\text{ }}\left[ {\because \cos {{108}^0} = - \cos {{72}^0}({\text{proved above}})} \right] \\

= \cos {36^0} \\

$

Which is equal to the RHS.

Hence, the given trigonometric equation is proved.

Note- In order to solve types of complex problems including some random angle values always try to use the trigonometric identities in order to solve the problem. Never try to find the value of such trigonometric terms. Whenever while solving if some known values of trigonometric terms appear, put into the values of such terms. Also keep in mind the part to be proved for an easy solution.

Complete step-by-step solution -

Given that: to prove $4\cos {12^0}\cos {48^0}\cos {72^0} = \cos {36^0}$

Since we know that

$2\cos A\cos B = \cos \left( {A + B} \right) + \cos \left( {A - B} \right)$

Taking the LHS part and proceeding further

$

LHS = 4\cos {12^0}\cos {48^0}\cos {72^0} \\

= 2 \times \left( {2\cos {{12}^0}\cos {{48}^0}} \right) \times \cos {72^0} \\

$

With the help of above formula simplifying the middle term

$

= 2 \times \left[ {\cos \left( {{{48}^0} + {{12}^0}} \right) + \cos \left( {{{48}^0} - {{12}^0}} \right)} \right] \times \cos {72^0} \\

= 2 \times \left[ {\cos \left( {{{60}^0}} \right) + \cos \left( {{{36}^0}} \right)} \right] \times \cos {72^0} \\

= 2\cos {60^0}\cos {72^0} + 2\cos {36^0} \times \cos {72^0} \\

$

Now substituting the value of know trigonometric quantity in the above equation

$

= 2 \times \dfrac{1}{2} \times \cos {72^0} + 2\cos {36^0}\cos {72^0}{\text{ }}\left[ {\because \cos {{60}^0} = \dfrac{1}{2}} \right] \\

= \cos {72^0} + 2\cos {36^0}\cos {72^0} \\

$

Again using the formula in second part

$

= \cos {72^0} + \left[ {\cos \left( {{{72}^0} + {{36}^0}} \right) + \cos \left( {{{72}^0} - {{36}^0}} \right)} \right] \\

= \cos {72^0} + \left[ {\cos {{108}^0} + \cos {{36}^0}} \right] \\

$

Also we know that

$

\cos \left( {180 - \theta } \right) = - \cos \theta \\

\Rightarrow \cos {108^0} = \cos \left( {{{180}^0} - {{72}^0}} \right) = - \cos {72^0} \\

$

So, substituting the value in above equation we have

$

= \cos {72^0} + \cos {108^0} + \cos {36^0} \\

= \cos {72^0} - \cos {72^0} + \cos {36^0}{\text{ }}\left[ {\because \cos {{108}^0} = - \cos {{72}^0}({\text{proved above}})} \right] \\

= \cos {36^0} \\

$

Which is equal to the RHS.

Hence, the given trigonometric equation is proved.

Note- In order to solve types of complex problems including some random angle values always try to use the trigonometric identities in order to solve the problem. Never try to find the value of such trigonometric terms. Whenever while solving if some known values of trigonometric terms appear, put into the values of such terms. Also keep in mind the part to be proved for an easy solution.

Recently Updated Pages

How many sigma and pi bonds are present in HCequiv class 11 chemistry CBSE

Why Are Noble Gases NonReactive class 11 chemistry CBSE

Let X and Y be the sets of all positive divisors of class 11 maths CBSE

Let x and y be 2 real numbers which satisfy the equations class 11 maths CBSE

Let x 4log 2sqrt 9k 1 + 7 and y dfrac132log 2sqrt5 class 11 maths CBSE

Let x22ax+b20 and x22bx+a20 be two equations Then the class 11 maths CBSE

Trending doubts

Which are the Top 10 Largest Countries of the World?

The 3 + 3 times 3 3 + 3 What is the right answer and class 8 maths CBSE

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

How many crores make 10 million class 7 maths CBSE

Difference Between Plant Cell and Animal Cell

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

Give 10 examples for herbs , shrubs , climbers , creepers

Change the following sentences into negative and interrogative class 10 english CBSE

Write a letter to the principal requesting him to grant class 10 english CBSE